Life skills (LPS): in the comprehensive and professional training of students (Revista Electrónica Calidad en la Educación Superior, 2025)
The purpose of this essay is to reflect on the importance of different cognitive, social, and emotional skills in the professional development of university students. This essay was based on a review of academic literature, which referenced the life skills approach proposed by the World Health Organization, its origin, concept, and classification, as well as its relationship to workplace competencies. This demonstrates that educational processes must be comprehensive and not solely focused on cognitive development. Therefore, teachers and students require these skills for their academic lives, both in the teaching and learning processes. It is evident that they are necessary for a healthy and balanced life beyond the workplace.
Keywords: life skills; cognitive skills; social skills; emotional management skills; comprehensive training; vocational training; higher education; training; job skills